ERK Nuclear Translocation Is Dimerization-independent but Controlled by the Rate of Phosphorylation - Lidke, Diane S.; Huang, Fang; Post, Janine N.; Rieger, Bernd; Wilsbacher, Julie; Thomas, James L.; Pouysségur, Jacques; Jovin, Thomas M.; Lenormand, Philippe (The Journal of biological chemistry, 2010)
Upon activation, ERKs translocate from the cytoplasm to the nucleus. This process is required for the induction of many cellular responses, yet the molecular mechanisms that regulate ERK nuclear translocation are not fully understood. We have used a mouse embryo fibroblast ERK1-knock-out cell line expressing green fluorescent protein (GFP)-tagged ERK1 to probe the spatio-temporal regulation of ERK1. Real time fluorescence microscopy and fluorescence correlation spectroscopy revealed that ERK1 nuclear accumulation increased upon serum stimulation, but the mobility of the protein in the nucleus and cytoplasm remained unchanged. Dimerization of ERK has been proposed as a requirement for nuclear translocation. However, ERK1-Δ4, the mutant shown consistently to be dimerization-deficient in vitro, accumulated in the nucleus to the same level as wild type (WT), indicating that dimerization of ERK1 is not required for nuclear entry and retention. Consistent with this finding, energy migration Förster resonance energy transfer and fluorescence correlation spectroscopy measurements in living cells did not detect dimerization of GFP-ERK1-WT upon activation. In contrast, the kinetics of nuclear accumulation and phosphorylation of GFP-ERK1-Δ4 were slower than that of GFP-ERK1-WT. These results indicate that the differential shuttling behavior of the mutant is a consequence of delayed phosphorylation of ERK by MEK rather than dimerization. Our data demonstrate for the first time that a delay in cytoplasmic activation of ERK is directly translated into a delay in nuclear translocation.